2009
DOI: 10.1080/09637480903022735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flaxseed gum on reduction of blood glucose and cholesterol in type 2 diabetic patients

Abstract: The effects of ingestion of flaxseed gum on blood glucose and cholesterol, particularly low-density lipoprotein cholesterol, in type 2 diabetes were evaluated. Flaxseed gum was incorporated in wheat flour chapattis. Sixty patients of type 2 diabetes were fed a daily diet for 3 months, along with six wheat flour chapattis containing flaxseed gum (5 g), as per the recommendations of the American Diabetic Association. The control group (60 individuals) consumed an identical diet but the chapattis were without gum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 31 publications
2
73
0
7
Order By: Relevance
“…Flaxseed fiber plays an important role in lowering the blood glucose levels. Studies demonstrated that insoluble fiber slows down the release of sugar in the blood and thus help in reducing blood glucose levels to great extent (Thakur et al 2009;Kapoor et al 2011). Soluble gum of the flaxseed may be helpful in the prevention of cardiovascular diseases by exhibiting hypocholesterolemic effect (Jenkins et al 1987;Cunnane et al 1994).…”
Section: Health Benefitsmentioning
confidence: 99%
“…Flaxseed fiber plays an important role in lowering the blood glucose levels. Studies demonstrated that insoluble fiber slows down the release of sugar in the blood and thus help in reducing blood glucose levels to great extent (Thakur et al 2009;Kapoor et al 2011). Soluble gum of the flaxseed may be helpful in the prevention of cardiovascular diseases by exhibiting hypocholesterolemic effect (Jenkins et al 1987;Cunnane et al 1994).…”
Section: Health Benefitsmentioning
confidence: 99%
“…However, due to its limited shelf-life, flaxseed was not used for human nutrition for a period of time. However, nowadays it gains attention worldwide as a functional food due to the findings that the consumption of flaxseed brings benefits to health, such as to help reducing the risk of occurrence of breast cancer, osteoporosis, diabetes, heart disease, and menopausal symptoms (DUFFY;CYR, 2003;DODIN et al, 2008;SACCO et al, 2009;THAKUR et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The high soluble fiber content is interesting for the nutritional point of view because it may decrease postprandial glucose absorption, improve glucose tolerance, and modulate serum cholesterol levels (CUNNANE et al, 1995;RICKARD;THAKUR et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Soluble fibre produces most of the anti-hypertensive benefits, accounting for 85 % of the fibre-associated decreases in SBP and 59 % in DBP [36]. In a randomized controlled trial, hypertensive, type 2 diabetic patients consuming 5 g/day of flaxseed gum (soluble mucilage) for 12 weeks noted substantial, yet insignificant, decreases in SBP, DBP and MAP (−16, −8 and −10 mm Hg) [37]. Higher doses of soluble fibre may be required to elicit significant anti-hypertensive action.…”
Section: Flaxseed Fibrementioning
confidence: 99%